1991
DOI: 10.1029/91jd01809
|View full text |Cite
|
Sign up to set email alerts
|

On the ozone minimum over the equatorial Pacific Ocean

Abstract: Since 1977, several ship and aircraft expeditions to the equatorial Pacific have reported extremely low (-<10 ppbv) or undetectable levels of ozone within the marine boundary layer. Of necessity, field programs from mobile platforms are limited in both their temporal and spatial coverage. However, a 10-year record of observations at the geophysical monitoring for climatic change site in American Samoa suggests that low ozone mixing ratios are a common occurrence and may reflect a spatially variable but permane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Over biomass burning regions with enhanced lower tropospheric ozone, the TOMS retrieval algorithm underestimates the ozone column by 3–5 DU. Over oceanic regions with ozone‐depleted air, the TOMS retrieval algorithm overestimates the ozone column by 2–5 DU; the largest overestimate occurs over the western Pacific where surface ozone concentrations are typically less than 20 ppbv (Figure 2c) [ Piotrowicz et al , 1991; Oltmans et al , 1998]. Efficiency corrections calculated from the simulation with reduced lightning emissions do not differ significantly from the values presented here.…”
Section: Correction To Toms Retrieval In the Lower Tropospherementioning
confidence: 67%
“…Over biomass burning regions with enhanced lower tropospheric ozone, the TOMS retrieval algorithm underestimates the ozone column by 3–5 DU. Over oceanic regions with ozone‐depleted air, the TOMS retrieval algorithm overestimates the ozone column by 2–5 DU; the largest overestimate occurs over the western Pacific where surface ozone concentrations are typically less than 20 ppbv (Figure 2c) [ Piotrowicz et al , 1991; Oltmans et al , 1998]. Efficiency corrections calculated from the simulation with reduced lightning emissions do not differ significantly from the values presented here.…”
Section: Correction To Toms Retrieval In the Lower Tropospherementioning
confidence: 67%
“…Thompson and Lenschow [1984] demonstrated that these low NO levels, given the high moisture and solar insolation of the equatorial Pacific (with appreciable production of OH), are consistent with a diurnal cycle of 03 increasing at night and decreasing during daytime. This diurnal pattern of surface 0 3 has been confirmed on a number of oceanographic expeditions in the remote Pacific since the mid-1980s [Piotrowicz et al, 1986[Piotrowicz et al, , 1991Johnson et al, 1990]. …”
Section: Introductionmentioning
confidence: 81%
“…Evidence for this picture of remote marine chemistry has been collected through trace gas measurements on a number of oceanographic cruises. Examples include the 1980 R/V Meteor cruise [Lowe and Schmidt, 1982], the 1987 Polarstern cruise [Rudolph and Johnen, 1990;Platt et al, 1992], and several NOAA/RITS (radiative!y important trace species) cruises [see Piotrowicz et al, 1986Piotrowicz et al, , 1991Johnson et al, 1990]. However, a comprehensive set of photochemically reactive trace gas measurements with sensitive instruments required for low concentrations has not been possible until recently.…”
Section: Introductionmentioning
confidence: 99%
“…Net photochemical destruction of ozone over the Pacific (Thompson et al 1993) leads to very low surface ozone (< 5 ppbv). Convective mixing of lowozone surface air can lead to low ozone concentrations aloft (Piotrowicz et al 1991) and a low-tropospheric ozone column.…”
mentioning
confidence: 99%